2003
DOI: 10.1590/s1676-06032003000100008
|View full text |Cite
|
Sign up to set email alerts
|

Diferenciação genética e diversidade em populações naturais de Cryptocarya aschersoniana Mez (Lauraceae)

Abstract: A variabilidade genética e estrutura de populações naturais de Cryptocarya aschersoniana Mez foram investigadas através de isoenzimas. Amostras de folhas de 267 indivíduos adultos foram coletadas de 12 populações procedentes de "Florestas de Planalto" do estado de São Paulo e sul de Minas Gerais, Brasil. A partir de 39 locos alozímicos polimórficos analisados, a divergência obtida através das estimativas de G ST sugerem a existência de deriva genética significativa e/ou de efeitos de seleção natural entre popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…For Ceratonia siliqua L. (Fabaceae), Makrem et al (2006) found an average value of 0.2. In Crytocarya aschersoniana Mez (Lauraceae), F ST values ranged between 0.279 and 0.395 (Moraes and Derbyshire 2003). For J. communis, a species closely related to J. brevifolia, Provan et al (2008) reported an average value of 0.103 in fragmented populations.…”
Section: Discussionmentioning
confidence: 99%
“…For Ceratonia siliqua L. (Fabaceae), Makrem et al (2006) found an average value of 0.2. In Crytocarya aschersoniana Mez (Lauraceae), F ST values ranged between 0.279 and 0.395 (Moraes and Derbyshire 2003). For J. communis, a species closely related to J. brevifolia, Provan et al (2008) reported an average value of 0.103 in fragmented populations.…”
Section: Discussionmentioning
confidence: 99%
“…The significance of the excess of genetic diversity (H e > H eq ) was estimated by the Wilcoxon signed rank test, with 5,000 randomized runs (Moraes and Derbyshire 2003), where H e is the expected heterozygosity under HardyWeinberg equilibrium and H eq is the expected heterozygosity under mutation and genetic drift equilibrium. This is considered the most appropriate test when few loci (<20) are used (Piry et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…High genetic variability levels have been reported for some Brazilian angiosperm species (Borba et al, F. Feres et al 2001;Moraes and Derbyshire, 2002;Telles et al, 2003;Souza et al, 2004). Also, genetic variability, higher within populations than among populations, has been reported (Moraes and Derbyshire, 2003;Botrel and Carvalho, 2004;Gusson et al, 2005), together with the absence of geographical and genetic correlation (Yanaka et al, 2005) for native species. All results for Brazilian species, including Wunderlichia mirabilis, suggest that for the majority of native species, genetic variability is higher within populations than among populations.…”
Section: Gene Genealogies and Population Differentiationmentioning
confidence: 95%